An exploratory study on turnover intention among private sector employees - Chan, Benjamin Yin Fah; Yeoh, Sok Foon; Lim, Chee Leong; Osman, Syuhaily (Canadian Center of Science and Education, 2010)
This study aims to study the organizational commitments, job stress, job satisfaction and turnover intention among the private sector employees in Petaling. A total of 120 respondents in Petaling District were selected conveniently. Organizational Commitments Questionnaire (Mowday, Steers & Porter, 1979), perceived Stress Scale (PSS), Minnesota Satisfaction Questionnaire (MSQ) and Mobley, Horner & Hollingsworth (1978) were used to measure organizational commitments, job stress, job satisfaction, and turnover intention. Majority of the respondents were single (77.5%), followed by married (20%), and divorced 2.5%. Results showed that majority of the respondents experienced moderate level of commitment (70.8%); half of the total respondents (50%) experienced high level of job stress; 67.5% of them experienced moderate level of job satisfaction and 42.5% of them experienced moderate level of turnover intention. The result uncovered that there was a significant negative relationship between organizational commitments and turnover intention in the study (r = -.367, p ≤ .05); positive relationship between job stress and turnover intention (r = .96, p ≤ .05) and negative relationship between job satisfaction and turnover intention in the study (r = -.447, p ≤ .01). Further analysis concluded that demographic background of respondent mediated the relationship between organizational commitments, job stress, job satisfaction and turnover intention. For future research, it is suggested to compare the predictive validity of the model across different jobs and industries. The methodology of study can be improved by increase the sample size to wider population and adopt probability sampling method in order to generalize more reliable results.